POTENTIAL FOR DEVELOPING A MARKETING STRATEGY FOR CITRONELLA OIL (Cymbopogon Nardus (L.) RENDLE IN PANGKATAN DISTRICT, LABUHANBATU CITY (CASE STUDY: SIDORUKUN VILLAGE) - Zulfida, Ida; Dewi, Dora Silvia (Fakultas Pertanian, Universitas Janabadra, 2023)
Citronella is a group of grass plants or the Poaceae family which is one of the producers of essential oil, namely citronella oil. Citronella oil has begun to be produced and marketed in Labuhanbatu Regency, Sidorukun Village, Pangkatan District. However, the citronella oil marketed is not yet optimal due to several factors that are obstacles. The objectives of studying the marketing strategy for citronella oil are to determine the internal and external factors in marketing citronella oil to determine the marketing strategy for citronella oil. The research methodology uses the SWOT analysis method where the analysis is presented as a marketing strategy for citronella oil, namely solving an environmental analysis by identifying existing strengths, weaknesses, opportunities and threats. The results of research with calculations using SWOT diagram analysis of the marketing of serei wangi oil are in the marketing strategy for serei wangi oil in Pangkatan District, namely establishing cooperation with the government to improve marketing. This strategy received the highest score, namely 7.02, by carrying out buying and selling transactions of serei wangi oil online. directly without intermediaries. This strategy can be implemented. This strategy gets the highest score, namely 6.74 and develops infrastructure and supporting facilities for the citronella oil agro-industry. This strategy gets the highest score, namely 5.98. Keywords: SWOT, Marketing of Serei Wangi Oil, Pangkatan District